2012
DOI: 10.1017/s0022029912000222
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intramammary infections and subclinical mastitis in post-partum dairy heifers

Abstract: The prevalence of intramammary infections (IMI) and subclinical mastitis (SCM) in 436 German Holstein heifers was put in relation with clinical findings of the udder and data regarding individual rearing and housing conditions of the animals. The clinical examination took place on the day of the livestock auction (at approximately 41 d in milk, DIM). On that day, 31% of the heifers had IMI in at least one quarter, and 18% of all quarters were infected. Coagulase-negative staphylococci were the most prevalent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Regular access to pasture (reported on 58% of the farms included here) was found to be a statistically significant protective factor associated with a reduced risk of mastitis (OR = 0.73, P = 0.047), which corresponds favorably with a German study in heifers where keeping the animals permanently housed increased their odds of developing subclinical mastitis by a factor of 4.86 (P = 0.004; Krömker et al, 2012). Similarly, a North American study demonstrated an increased prevalence of mastitis in both Holstein and Jersey cows when kept indoors compared with those permitted access to pasture (Washburn et al, 2002).…”
Section: Discussionsupporting
confidence: 79%
“…Regular access to pasture (reported on 58% of the farms included here) was found to be a statistically significant protective factor associated with a reduced risk of mastitis (OR = 0.73, P = 0.047), which corresponds favorably with a German study in heifers where keeping the animals permanently housed increased their odds of developing subclinical mastitis by a factor of 4.86 (P = 0.004; Krömker et al, 2012). Similarly, a North American study demonstrated an increased prevalence of mastitis in both Holstein and Jersey cows when kept indoors compared with those permitted access to pasture (Washburn et al, 2002).…”
Section: Discussionsupporting
confidence: 79%
“…The association between the prevalence of mastitis and age at first calving was in disagreement with Kromker et al (2012), who reported that older heifers at first calving were more likely than younger heifers to have mastitis.…”
Section: Risk Factorsmentioning
confidence: 59%
“…For most of the heifer's life, the mammary gland has been immature and it would seem less likely to be in close physical contact to the environment, as contrasted with multiparous cattle. There are a few risk factors identified by several researchers that influence the prevalence of heifer clinical mastitis (HCM) and heifer subclinical mastitis (HSCM) such as herd size, floor type, juvenile intersucking, removing supernumerary teats, age at first calving, location of close-to-calving heifers, number of calves, udder and/or teat wounds, unhygienic udder postcalving, milk production, blocked milk secretion during the first milking, and oxytocin administration necessary for the first milking (Parker et al 2007a;Kromker et al 2012;Santman-Berends et al 2012). However, mastitis is a multifactorial disease, requiring exposure to a combination of environmental and pathogenic factors and with variable responses between animals.…”
Section: Introductionmentioning
confidence: 99%
“…IMI prior to calving and in the early lactation may interfere with the development of the mammary glands, the future milk production, udder health, and related culling hazards [12]. An IMI at calving also increases the risk of clinical mastitis (CM) within the first week after calving [13]. Edinger et al [14] found that mastitis prior to calving and mastitis within the first week after calving increased the risk of further cases of mastitis and culling during the first 45 days of lactation.…”
Section: Introductionmentioning
confidence: 99%